Effects of parental mental illness on children's physical health: systematic review and meta-analysis - Pierce, Matthias; Hope, Holly F.; Kolade, Adekeye; Gellatly, Judith; Osam, Cemre Su; Perchard, Reena; Kosidou, Kyriaki; Dalman, Christina; Morgan, Vera; Di Prinzio, Patricia; Abel, Kathryn M. (British journal of psychiatry, 2020)
Children of parents with mental disorder face multiple challenges. To summarise evidence about parental mental disorder and child physical health. We searched seven databases for cohort or case-control studies quantifying associations between parental mental disorders (substance use, psychotic, mood, anxiety, obsessive-compulsive, post-traumatic stress and eating) and offspring physical health. Studies were excluded if: they reported perinatal outcomes only (<28 days) or outcomes after age 18; they measured outcome prior to exposure; or the sample was drawn from diseased children. A meta-analysis was conducted. The protocol was registered on the PROSPERO database (CRD42017072620). Searches revealed 15 945 non-duplicated studies. Forty-one studies met our inclusion criteria: ten investigated accidents/injuries; eight asthma; three other atopic diseases; ten overweight/obesity; ten studied other illnesses (eight from low-and middle-income countries (LMICs)). Half of the studies investigated maternal perinatal mental health, 17% investigated paternal mental disorder and 87% examined maternal depression. Meta-analysis revealed significantly higher rates of injuries (OR = 1.15, 95% CI 1.04-1.26), asthma (OR = 1.26, 95% CI 1.12-1.41) and outcomes recorded in LMICs (malnutrition: OR = 2.55, 95% CI 1.74-3.73; diarrhoea: OR = 2.16, 95% CI 1.65-2.84). Evidence was inconclusive for obesity and other atopic disorders. Children of parents with mental disorder have health disadvantages; however, the evidence base is limited to risks for offspring following postnatal depression in mothers and there is little focus on fathers in the literature. Understanding the physical health risks of these vulnerable children is vital to improving lives. Future work should focus on discovering mechanisms linking physical and mental health across generations. None.